ROLE OF SPORT TOURISM IN UZBEKISTAN’S LOCAL TOURISM MARKET (American Journal of Interdisciplinary Research and Development, 2024)
Local sporting activities have evolved into vehicles for promoting the local tourism market and economic development in the communities where they take place. Knowing the specific profile of the athletes who participate in them, recognizing their expectations, and providing them with good experiences is critical for maximizing the benefits that these events may bring to the destinations. In this regard, the goal of this study was to determine the characteristics of the destination and event that had the greatest influence on participants' enjoyment. The study's findings revealed that the presence or absence of athlete fellow companions has an important impact on the destination characteristics that influence athlete pleasure. They also discovered that the quality of the journey, the professionalism of the organization and volunteers, the implementation of environmental protection measures, and the quality of the refreshment facilities are the event-related factors that have the greatest influence on participant satisfaction. The destination's environmental and natural attractions, as well as the surroundings and atmosphere, were shown to be the most influential factors.